The critical issues of SiC materials for future nuclear systems. (15th January 2018) - Li, Mian; Zhou, Xiaobing; Yang, Hui; Du, Shiyu; Huang, Qing
Abstract: SiC ceramic and SiC-based composites are promising structural materials for nuclear applications. This paper gives a viewpoint of the basic characterization and research-highlights of SiC-based composites with respect to applications in future nuclear systems. In particular, the following aspects are considered: 1) SiC fiber, 2) interphase, 3) SiC matrix, and 4) SiC joining. Furthermore, remaining challenges and specific technical issues of SiC-based composites for nuclear applications are discussed, and some suggestions to overcome these are proposed. Graphical abstract: Image 1